Prevalence and Pregnancy Outcome of Gestational Diabetes Mellitus Among Bangladeshi Urban Pregnant Women (Journal of Medicine, 2012)
Objective: To assess the prevalence of gestational diabetes mellitus (GDM) among the pregnant women of Dhaka city and to find out the consequences or effects of GDM on pregnancy outcome. Materials and methods: This was a descriptive type of cross sectional study followed by cohort type of study, conducted in different hospitals in Dhaka city. Initially 960 pregnant women of 24th to 28th weeks were selected purposively; plasma glucose was measured at fasting and two hours after taking 75g oral glucose load. Modified method of Carpenter and Coustan criteria was followed to diagnose GDM. For each GDM case diagnosed, one non-GDM pregnant women was taken as control after matching age and parity. Both groups were followed up to 4 wks after delivery to find out maternal and neonatal mortality and morbidities. Results: Out of 960 pregnant women 72 were GDM positive (7.5%).There was no maternal mortality but morbidities like hydramnions (p